Working in Hollywood : how the studio system turned creativity into labor - Regev, Ronny (North Carolina scholarship online., 2018)
This work reveals an important untold story of an influential twentieth-century workplace. Ronny Regev argues that the Hollywood studio system institutionalized creative labour by systemizing and standardizing the work of actors, directors, writers, and cinematographers, meshing artistic sensibilities with the efficiency-minded rationale of industrial capitalism.